The Effect of Capital Intensity, Inventory Intensity, and Transfer Pricing on Tax Avoidance: Evidence from Consumer Goods Companies Listed on the Indonesia Stock Exchange for the Period 2020–2024 - Robiha, Robiha; Hartono, Hartono (SEAN Institute, 2025)
This study investigates the influence of capital intensity, inventory intensity, and transfer pricing on tax avoidance in consumer goods companies listed on the Indonesia Stock Exchange. Employing a descriptive quantitative approach, this research utilizes secondary data obtained from annual financial reports. Panel data regression analysis is applied to examine the proposed hypotheses. The findings demonstrate that capital intensity, inventory intensity, and transfer pricing each significantly affect tax avoidance practices. These results support the theoretical assumptions of agency theory and positive accounting theory, suggesting that managerial discretion in financial and operational strategies influences tax-related decisions. The study contributes to the growing literature on corporate tax behavior by emphasizing how internal company characteristics and pricing policies shape tax avoidance tendencies. Moreover, it provides valuable implications for tax authorities, policymakers, and corporate stakeholders in enhancing transparency and improving regulatory frameworks. Future research is encouraged to explore additional variables and extend the model across other industrial sectors.